PENGARUH INDEKS TATA KELOLA PERUSAHAAN TERHADAP AKUN PAJAK TANGGUHAN DAN TINGKAT PENGEMBALIAN SAHAM (Studi Kasus pada Perusahaan Sektor Teknologi di Bursa Efek Indonesia Tahun 2020-2023) - Anggita Putri Maharani; Endang Kiswara (Diponegoro Journal of Accounting, 2025)
This study was conducted to examine the effect of the Corporate Governance Index (CGI) on Deferred Tax Accounts and Stock Return, also adding control variables such as Sales Growth, Profitability, Leverage, and Capital Expenditure. This research refers to research of Abdelfattah, T., Aboud, A. (2020) which is updated by using a sample of technology sector companies on the Indonesia Stock Exchange in 2020-2023.This study uses secondary data with samples taken using a double sampling method. The final sample obtained was 9 technology sector companies listed on the Indonesia Stock Exchange in 2020-2023 with a total of 36 observations. This study uses the panel data regression analysis method in the Eviews13 application to test the hypothesis regarding the effect of the Corporate Governance Index on Deferred Tax Accounts and Stock Returns.The results showed that the corporate governance index has a significant positive effect on deferred tax accounts on deferred asset side. Meanwhile, the corporate governance index has no significant effect on stock return.